GE_GERICHTE C/4364/2014 vom 19. November 2019 - GE Cour de justice (2019)
ACTION EN DIVORCE;OBLIGATION D'ENTRETIEN;ENFANT;CONJOINT;VISITE;PRÉVOYANCE PROFESSIONNELLE | CPC.58; CPC.58.al2; CC.7d.al2; CC.124.letb.ch3; CC.125; CC.273.al1; CC.276; CC.285